2008
DOI: 10.1111/j.1532-5415.2007.01539.x
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthy Drinking Patterns in Older Adults: Prevalence and Associated Characteristics

Abstract: Almost one in 10 elderly Medicare beneficiaries report exceeding recommended drinking limits. Several distinct unhealthy drinking patterns were identified and associated with sociodemographic and health characteristics, suggesting the value of additional targeted approaches within the context of universal screening to reduce alcohol misuse by older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
165
8
5

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(205 citation statements)
references
References 34 publications
27
165
8
5
Order By: Relevance
“…Nine percent of elderly Medicare beneficiaries (2003 data) reported at-risk drinking defined as either exceeding 30 drinks in a typical month in the past year or heavy episodic drinking (drinking four or more drinks on a single day). 12 In a study using 2005 and 2006 data from the National Survey on Drug Use and Health, 13 % of men and 8 % of women aged 65 and older reported drinking two or more drinks per day. 13 Although low to moderate levels of alcohol use can have health benefits, [14][15][16][17][18] the exact benefit dose is not known and may not be risk free.…”
Section: Introductionmentioning
confidence: 99%
“…Nine percent of elderly Medicare beneficiaries (2003 data) reported at-risk drinking defined as either exceeding 30 drinks in a typical month in the past year or heavy episodic drinking (drinking four or more drinks on a single day). 12 In a study using 2005 and 2006 data from the National Survey on Drug Use and Health, 13 % of men and 8 % of women aged 65 and older reported drinking two or more drinks per day. 13 Although low to moderate levels of alcohol use can have health benefits, [14][15][16][17][18] the exact benefit dose is not known and may not be risk free.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Among late middle-aged U.S. adults (45-65 years), prevalence of past-year alcohol abuse or dependence is estimated to be 8.2 % for males and 2.9 % for females, 2,12 4-5 % of adults 55 and older report binge drinking in the past month, 13 and 9 % of adults over age 65 consume alcohol in excess of national guidelines. 14 Older adults may be more vulnerable to the negative health effects of alcohol than their younger counterparts due, in part, to interactions with prescription medications and less efficient metabolism of alcohol, which results in older adults having higher blood alcohol levels than younger adults after consuming a similar amount. 7,15,16 The population attributable risk of these vulnerabilities will increase sharply with the aging of the population coupled with possibly higher drinking levels in the baby boomer and younger cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…The differences between young adults and the elderly are so marked that it has been suggested that the latter should drink no more than only one drink per day, if there are no absolute contraindications due to the presence of some disease or use of medication 6 . In spi-te of these higher risks, it is estimated that 9% of elderly people in the USA have an unhealthy drinking habit 7 .…”
Section: Introductionmentioning
confidence: 99%